+0  
 
0
97
2
avatar

sinh^-1 (1)

Guest Sep 14, 2017
Sort: 

2+0 Answers

 #1
avatar+7118 
0

sinh^-1 (1)

 

\(sinh^{-1}(1°)_{deg}=asinh(1°)_{deg}\color{blue}=50.498986710526\\ sinh^{-1}(1)_{rad}=asinh(1)_{rad}\color{blue}=0.88137358702\)

 

laugh  !

asinus  Sep 14, 2017
edited by asinus  Sep 14, 2017
 #2
avatar+18715 
0

hyperbolic functions

\(sinh^{-1} (1)\)

 

Formula:

\(\begin{array}{|rcll|} \hline sinh(z) &=& \frac{e^z-e^{-z}}{2} \\ z &=& sinh^{-1} (\frac{e^z-e^{-z}}{2} ) \\ \hline \end{array}\)

 

\(z=\ ?\)

\(\begin{array}{|rcll|} \hline \frac{e^z-e^{-z}}{2} &=& 1 \\ e^z-e^{-z} &=& 2 \\ e^z-\frac{1}{e^{z}} &=& 2 \quad & | \quad \text{substitute } e^z = x \\ x-\frac{1}{x} &=& 2 \quad & | \quad \cdot x \\ x^2-1 &=& 2x \\ x^2-2x-1 &=& 0 \\\\ x &=& \frac{2\pm \sqrt{4-4\cdot(-1)} }{2} \\ &=& \frac{2\pm \sqrt{8} }{2} \\ &=& \frac{2\pm \sqrt{2\cdot 4 } }{2} \\ &=& \frac{2\pm 2\sqrt{2} }{2} \\ \mathbf{x} &\mathbf{=}& \mathbf{1\pm \sqrt{2}} \quad & | \quad x = e^z \\ e^z & = & 1\pm \sqrt{2} \quad & | \quad \ln() \\ z & =& \ln(1\pm \sqrt{2}) \\\\ z_1 &=& \ln(1 + \sqrt{2}) \\ z_2 &=& \ln(1 - \sqrt{2}) \quad & | \quad \text{no solution } \quad 1 - \sqrt{2} < 0! \\\\ \mathbf{sinh^{-1} (1)= z} &\mathbf{=}& \mathbf{\ln(1 + \sqrt{2})} \\ \mathbf{sinh^{-1} (1) } &\mathbf{=}& \mathbf{0.88137358702\ldots} \\ \hline \end{array}\)

 

laugh

heureka  Sep 14, 2017

14 Online Users

avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details